2021
DOI: 10.3389/fcimb.2021.585919
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Peripheral Blood Transcriptome Datasets Reveals a Biomarker Panel for Tuberculosis in Patients Infected With HIV

Abstract: Biomarkers are critical for rapid diagnosis of tuberculosis (TB) and could benefit patients with AIDS where diagnosis of TB co-infection is challenging. Meta-analysis is an approach to combine the results of the studies with standard statistical method by weighting each study with different sample size. This study aimed to use meta-analysis to integrate transcriptome datasets from different studies and screen for TB biomarkers in patients who were HIV-positive. Five datasets were subjected to meta-analysis on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The latest study used meta-analysis to integrate transcriptome datasets from different studies and screen for TB biomarkers in patients who were HIV-positive [ 15 ]. In our study, we will analyse data for PTB while eliminating any potential interference from HIV by using HIV-negative patients only.…”
Section: Introductionmentioning
confidence: 99%
“…The latest study used meta-analysis to integrate transcriptome datasets from different studies and screen for TB biomarkers in patients who were HIV-positive [ 15 ]. In our study, we will analyse data for PTB while eliminating any potential interference from HIV by using HIV-negative patients only.…”
Section: Introductionmentioning
confidence: 99%
“…A challenging issue in HIV-TB coinfection is the atypical presentation of TB [ 40 ]. While the conventional sputum-based detection of TB is of limited scope in these patients and often leads to false negativity [ 41 ], interferon gamma (IFN-γ)-based assays, though specific [ 42 ], are more expensive. Thus, several studies have applied transcriptomics, particularly the altered or differentially expressed protein-coding genes between HIV and HIV-TB patients, to identify biological markers for TB in HIV patients [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several hub-central TFs, including ATF3 ( Chen Y. et al, 2021 ), FOSB ( Green et al, 2010 ), HIF1A ( Li F. et al, 2020 ), and IRF1 ( Pathak et al, 2007 ) were also identified that played a key immunoregulatory role in the biological behavior of the pink module. For example, HIF1A hub-central TF is a master transcriptional regulator and an important factors in regulating gene expression in response to hypoxia ( Cimmino et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%